2023
DOI: 10.1111/brv.12947
|View full text |Cite
|
Sign up to set email alerts
|

Forests are critically important to global pollinator diversity and enhance pollination in adjacent crops

Abstract: Although the importance of natural habitats to pollinator diversity is widely recognized, the value of forests to pollinating insects has been largely overlooked in many parts of the world. In this review, we (i) establish the importance of forests to global pollinator diversity, (ii) explore the relationship between forest cover and pollinator diversity in mixed‐use landscapes, and (iii) highlight the contributions of forest‐associated pollinators to pollination in adjacent crops. The literature shows unambig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 254 publications
1
30
0
Order By: Relevance
“…While management practices that restore pollinator communities in some working landscapes (especially agriculture) are well‐established (e.g., Kremen et al, 2019), our understanding of how to manage intensively managed forests for pollinators lags behind (Rivers, Galbraith, et al, 2018). This is likely because, until recently, forests were not seen as providing suitable habitat for bees (Rivers & Betts, 2021; Ulyshen et al, 2023). Our study and others have shown that intensively managed forests can support diverse and abundant bee and flowering plant communities (Rivers & Betts, 2021; Zitomer et al, 2023), and that management to enhance floral diversity may be able to bolster the utility of these forests for bee conservation.…”
Section: Discussionmentioning
confidence: 99%
“…While management practices that restore pollinator communities in some working landscapes (especially agriculture) are well‐established (e.g., Kremen et al, 2019), our understanding of how to manage intensively managed forests for pollinators lags behind (Rivers, Galbraith, et al, 2018). This is likely because, until recently, forests were not seen as providing suitable habitat for bees (Rivers & Betts, 2021; Ulyshen et al, 2023). Our study and others have shown that intensively managed forests can support diverse and abundant bee and flowering plant communities (Rivers & Betts, 2021; Zitomer et al, 2023), and that management to enhance floral diversity may be able to bolster the utility of these forests for bee conservation.…”
Section: Discussionmentioning
confidence: 99%
“…Temporal mismatch between floral nutritional availability and native bee foraging activity (Figure 1) can decouple ecological networks and result in species loss (Kudo & Ida, 2013; Ogilvie & Forrest, 2017), as bees must be able to access floral protein sources (pollen) for brood provisioning in order to maximise fitness. For example, there is increasing recognition of the importance of resources from canopy trees and spring ephemerals (Ulyshen et al, 2023), particularly for early emerging bees such as queen bumblebees (Mola, Hemberger, et al, 2021), but early season forest plants may be declining hence adding stress to critical bee life stages (Mola, Richardson, et al, 2021). These temporal shifts in both floral bloom and bee activity periods are highly species‐specific and poorly understood (Solga et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…are larval host plants for hundreds of caterpillar species (Narango et al 2020). In summary, the greatest pollinator diversity is supported by a healthy forested-landscape with a balance of age classes to support varying species specific and life cycle needs (Ulyshen et al 2023).…”
Section: Introductionmentioning
confidence: 99%